Design of Proactive Management System for Residential Buildings by Using Smart Equipment - Savytskyi, Mykola V.; Shekhorkina, Svitlana; Bordun, Maryna; Babenko, Maryna; Tsyhankova, Svitlana; Spyrydonenkov, Vitalii; Savytskyi, Oleksandr M.; Rabenseifer, Roman (TECHNOLOGY CENTER PC, Kharkiv, 2023)
ENG: This study's object is an energy efficiency of residential sector. The work is aimed at solving the task to improve the energy efficiency of the housing sector by devising technical solutions for monitoring and managing energy consumption and microclimate parameters of buildings. The proposed proactive management system for residential buildings consists of multi-sensors measuring CO2, temperature and humidity, smart meters of heat and electricity consumption, and smart plugs. The equipment is combined into single system through an integration controller with remote user access through an interactive web interface. A feature of the technical solution is the ability to collect, process, visualize, and archive data on the consumption of energy, as well as on the key parameters of the microclimate of residential premises. The advantages of the system are its flexibility due to the possibility of integrating additional devices during operation, as well as the use of standard communication protocols, which enables the interchangeability of component elements. The implementation and testing were carried out under the conditions of a real pilot site. The use of the system in practice confirmed the efficiency and stability of the operation, making it possible to obtain data on the parameters of energy consumption and microclimate and devising recommendations for reducing energy consumption at the pilot site. It was established that the microclimate meets the requirements of the standards (air temperature is about 22 °С while relative humidity does not exceed 60 %). Decrease in energy consumption can be achieved by reducing the temperature of the heat carrier in the absence of residents, as well as by considering the influence of weather conditions. During periods of residents’ activity, an excess of the permissible level of CO2 was recorded, therefore, automatic ventilation systems should be provided in the apartments.

UKR: Об’єкт дослідження – енергоефективність житлового сектору. Робота спрямована на вирішення проблеми підвищення енергоефективності житлового сектору шляхом розробки технічних рішень з моніторингу та управління енергоспоживанням та параметрами мікроклімату будівель. Запропонована проактивна система менеджменту житлових будівель складається з мультисенсорів СО2, температури та вологості, смарт-лічильників споживання теплової та електроенергії та смарт-розеток. Обладнання об’єднується в одну систему через інтеграційний контролер із віддаленим доступом користувача через інтерактивний веб-інтерфейс. Особливістю технічного рішення є можливість збору, обробки, візуалізації та архівування даних щодо споживання енергії та одночасно про ключові параметри мікроклімату житлових приміщень. Перевагами системи є можливість інтеграції додаткових приладів в процесі експлуатації та використання стандартних протоколів роботи, що забезпечує взаємозамінність складових елементів. Реалізація та тестування виконані в умовах реального пілотного об’єкта. Використання системи на практиці підтвердило працездатність та стабільність роботи, дозволило отримати дані про параметри енергоспоживання та мікроклімату та запропонувати рекомендації для зниження витрат енергії. Встановлено, що мікроклімат відповідає вимогам стандартів (температура повітря близько 22 °С та відносна вологість не перевищує 60 %). Зниження витрат енергії може бути досягнуто шляхом зменшення температури теплоносія при відсутності мешканців та врахуванням погодних умов. В періоди активної діяльності мешканців зафіксовано перевищення допустимого рівня СО2, тому слід передбачити автоматичні системи вентиляції.
Розробка системи проактивного менеджменту житлових будівель на основі смарт-обладнання
M. Savytskyi: ORCID 0000-0003-3325-4675; O. Savytskyi: ORCID 0009-0008-7032-295X
Keywords: energy efficiency; energy management; residential building; smart equipment; internet of things; energy demand; occupants’ well-being; енергоефективність; енергоменеджмент; житлова будівля; смарт-обладнання; інтернет речей; енергоспоживання; комфорт мешканців; TECHNOLOGY::Civil engineering and architecture